2016
DOI: 10.3109/14397595.2016.1158896
|View full text |Cite
|
Sign up to set email alerts
|

Renal outcomes in mixed proliferative and membranous lupus nephritis (Class III/IV + V): A long-term observational study

Abstract: This study demonstrated a combination of proliferative and membranous LN (ISN/RPS Class III/IV + V) predicts poor renal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Other studies also identified gender, proteinuria and histological class to affect renal progression. Among the eight patients seronegative for both ANA and anti‐dsDNA, four had membranous lupus nephropathy.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Other studies also identified gender, proteinuria and histological class to affect renal progression. Among the eight patients seronegative for both ANA and anti‐dsDNA, four had membranous lupus nephropathy.…”
Section: Discussionmentioning
confidence: 96%
“…32 It is thus important to minimise occurrence and duration of flares with adequate immunosuppressive therapy, balanced against the risk of immunosuppressant-related complications such as infections. 33 Other studies also identified gender, 13,26,34 proteinuria 13,26,29 and histological class 25 to affect renal progression. Among the eight patients seronegative for both ANA and anti-dsDNA, four had membranous lupus nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lupus nephritis (LN) is one of multiple organ manifestations of SLE, and is an important prognostic factor [1]; therefore, new, improved therapeutic approaches and biomarkers are needed. Urine protein and serum creatinine (Cre) are traditionally used as markers of LN.…”
Section: Introductionmentioning
confidence: 99%